(untitled) (Research, Society and Development, 2021)
Thiamine (vitamin B1) is a water-soluble vitamin, an essential micronutrient, naturally occurring. Humans do not synthesize thiamine, its supply in the human body depends almost entirely on food intake. The lactate dosage is an indirect indicator of thiamine deficiency. This is a clinical study to evaluate the intake of thiamine in patients from the Emergency Room, its relation to the normal feed intake, and indirect measures of activity vitamin B1 according to serum lactate. In a cross-sectional study, 15 patients (GPS) underwent collection of blood lactate, arterial blood gases, usual food recall, verified the underlying disease, symptoms, nosographic data, medications, food intake and alcohol intake. The control group (CG), 22 individuals, was submitted by the usual food recall. From the GPS, the adequacy for dietary intake of thiamine did not show any significant difference with the CG. There was significant correlation between lactate and thiamine (r = -0.60) and between fat intake and thiamin (r = 0.72) but not total energy, carbohydrates and protein. The food intake of the participants (GPS and CG) equipped with a higher frequency of fish, chicken, flour and white rice. The data suggest a low intake of thiamine. These data may justify the availability of vitamins for hospital pharmacotherapeutic treatment and new, broader studies may support the hypothesis of thiamine supplementation in commonly consumed foods (eg flour), for the population of Manaus, associated with measures of guidance.